Pharmaceutical statistics : practical and clinical applications - Bolton, Sanford, 1929-2011. (New York : M. Dekker, 1997)
This edition offers new and expanded information on developments in the field of pharmaceutical statistics. College and university bookstores may order five or more copies at a special student price which is available upon request from Marcel Dekker.
Basic definitions and concepts -- Data graphics -- Introduction to probability: the binomial and normal probability distributions -- Choosing samples -- Statistical inference: estimation and hypothesis testing -- Sample size and power -- Linear regession and correlation -- Analysis of variance -- Factoral designs -- Transformations and outliers -- Experimental design in clinical trials -- Quality control -- Validation -- Consumer testing -- Nonparametric methods -- Optimiaztion techniques -- Appendix 1. Some properties of the variance -- Appendix 2. Comparison of slopes and testing of linearity: determination of relative potency -- Appendix 3. Multiple regression -- Appendix 4. Tables -- Appendix 5. Outlier tests and chemical assays -- Appendix 6. Should a single unexplained failing assay be reason to reject a batch? -- Answers to exercises -- Index.
Includes bibliographical references and index.
Keywords: Pharmacy -- Statistical methods; Technology, Pharmaceutical -- methods -- laboratory manuals; Statistics as Topic -- laboratory manuals